2002
DOI: 10.1038/sj.gene.6363846
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors in the NFκB cascade comprise prime candidate genes predisposing to multiple sclerosis, especially in selected combinations

Abstract: Multiple sclerosis (MS) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 25 publications
1
58
1
1
Order By: Relevance
“…Many polymorphisms of the NFKBIA gene have been identified;recently, these polymorphisms have attracted widespread attention [13]. A number of case-control studies have been conducted to investigate the association of these polymorphisms with autoimmune and inflammatory diseases [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, these studies reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Many polymorphisms of the NFKBIA gene have been identified;recently, these polymorphisms have attracted widespread attention [13]. A number of case-control studies have been conducted to investigate the association of these polymorphisms with autoimmune and inflammatory diseases [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, these studies reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…54 Public domain databases (Japanese JSNP, http://snp.ims.utokyo.ac.jp, NCBI's dbSNP, http://www.ncbi.nlm.nih.-gov/SNP/) and SNPSelector 55 were used to identify SNPs from the following five plausible MS candidate genes that were located 260 kb centromeric and 120 kb telomeric of APOE: PVR (poliovirus receptor, MIM 173850), CBLC (Cas-Br-M (murine) ecotropic retroviral transforming sequence c, MIM 608453), PVRL2 (polio- 56,57 CBLC and RELB were selected because they are believed to regulate the NF-kB cascade, which has previously been implicated in MS, [58][59][60] and PVR and PVRL2 were of particular interest because viral infections have long been suspected to be environmental triggers of MS. 43,[61][62][63] Genotype data from the HapMap project (http:// www.hapmap.org) were used for SNP validation and for visual inspection of the LD structure in this region of the genome. All SNP genotypes, including the two SNPs in exon 4 of the APOE gene that define the three functional APOE alleles commonly referred to as e2, e3 and e4, were generated by the TaqMan allelic discrimination assay on an ABI7900HT genotyping platform.…”
Section: Snp Selection and Genotyping Methodsmentioning
confidence: 99%
“…One of the first indications of the importance of this pathway in MS pathogenesis came from a candidate gene study approach which identified both MS predisposing and protective alleles within NF-kB inhibitor genes (NF-kBIL1, predisposing; NF-kBIA, protective) [153]. However, in a study of peripheral blood mononuclear cells from MS patients, no abnormalities in NF-kB activity were observed between patients and controls [154].…”
Section: Hats Hdacs and The Nf-kb Pathwaymentioning
confidence: 99%